Peran Inovasi dalam Memanfaatkan Teknologi Digital untuk Pertumbuhan Ekonomi di Probolinggo - Arief Rachman Afandy; Zainul Abidin; M Rizal; Abdul Hamid (Universitas 45 Surabaya, 2025)
The development of innovation and technology is the key to creating a more inclusive, efficient, and sustainable economic growth model in today's digital era. In an era where digital connectivity has become the norm, the role of technological innovation for economic growth cannot be underestimated. This article aims to explore the potential and challenges in utilizing digital technology with a focus on the agricultural and tourism sectors for economic growth in Probolinggo Regency. Based on a qualitative approach, by collecting data through literature studies from various journals and other relevant sources. Digital technology based on innovation has great potential to increase efficiency and productivity in the agricultural sector, such as through the use of the Internet of Things (IoT) for crop monitoring, as well as the tourism sector through the concept of e-tourism. However, the implementation of digital technology in Probolinggo is hampered by a lack of infrastructure, low digital literacy, and the gap in access between urban and rural areas. In addition, local government policies that do not fully support the development of the digital economy are also obstacles. This article concludes that technology and innovation are the keys to achieving inclusive and sustainable economic growth in the digital era.